2008
DOI: 10.1111/j.1365-2249.2008.03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to a C-terminal fragment of the Plasmodium falciparum blood-stage antigen Pf332 in Senegalese individuals naturally primed to the parasite

Abstract: SummaryPrevious studies have shown that antibodies from humans exposed continuously to malaria recognize the Plasmodium falciparum asexual blood-stage antigen Pf332. Here we analysed the antibody responses to a C-terminal fragment of Pf332, designated C231, in individuals from Senegal, by measuring the serum levels of immunoglobulin M (IgM), IgG class and subclass and IgE antibodies. IgG antibody reactivity with crude P. falciparum antigen was detected in all the donors, while many of the children lacked or ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies using recombinant protein of the Pf332 regions EB200 and C231 (a C-terminally located region of Pf332, less rich in degenerate-repeats [ 47 ]), have reported that children lack antibodies against both parts of the molecule. However, antibodies were frequently found in older individuals, indicating a slow acquisition of Pf332 antibodies [ 14 , 48 ]. Our results show that children living in Apac, a highly endemic region in Uganda experiencing the highest entomological inoculation rate reported in Africa [ 29 ], had developed antibodies to both Pf332-DBL and PfEMP1-DBL already at a very young age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using recombinant protein of the Pf332 regions EB200 and C231 (a C-terminally located region of Pf332, less rich in degenerate-repeats [ 47 ]), have reported that children lack antibodies against both parts of the molecule. However, antibodies were frequently found in older individuals, indicating a slow acquisition of Pf332 antibodies [ 14 , 48 ]. Our results show that children living in Apac, a highly endemic region in Uganda experiencing the highest entomological inoculation rate reported in Africa [ 29 ], had developed antibodies to both Pf332-DBL and PfEMP1-DBL already at a very young age.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the measurement of specific antibodies has been done by the enzyme-linked immunosorbent assay (ELISA) 2325 . Although this classical technique has been very useful over the years, it demands significant amount of time, the use of relatively large sample volumes and, importantly, only allows quantifying antibodies against a single antigen at a time.…”
Section: Introductionmentioning
confidence: 99%